2014
DOI: 10.1038/modpathol.2013.133
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of TP53 and cytokeratin 7 immunohistochemistry in idiopathic inflammatory bowel disease-associated neoplasia

Abstract: Long-standing inflammatory bowel disease is associated with increased risk of developing colorectal adenocarcinoma. Significant intra-and inter-observers' variability exists in histologic interpretation of dysplasia in surveillance biopsies. In this study, we evaluated the utility of a panel of immunohistochemical markers in diagnosing inflammatory bowel disease-associated neoplasia. We reviewed 39 colectomy specimens with inflammatory bowel disease-associated neoplasia. In these 39 cases, we identified 172 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…We performed immunohistochemistry for p53 and cytokeratin 7 in 44 cases of colon biopsies with IBD-IND and investigated the value of these two markers in predicting neoplastic progression in IBD-IND because our previous study showed overexpression of p53 and cytokeratin 7 in IBD-associated neoplasia in a partially overlapping and partially complementary fashion [ 17 ]. In our current cohort of IBD patients with IND, 27% of cases had ≥ 5% epithelial nuclei with intense p53 expression; this rate is comparable with the results of a previous study that found 21% of colon biopsies with IND showed intense nuclear p53 immunoreactivity in ≥ 5% epithelial nuclei [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed immunohistochemistry for p53 and cytokeratin 7 in 44 cases of colon biopsies with IBD-IND and investigated the value of these two markers in predicting neoplastic progression in IBD-IND because our previous study showed overexpression of p53 and cytokeratin 7 in IBD-associated neoplasia in a partially overlapping and partially complementary fashion [ 17 ]. In our current cohort of IBD patients with IND, 27% of cases had ≥ 5% epithelial nuclei with intense p53 expression; this rate is comparable with the results of a previous study that found 21% of colon biopsies with IND showed intense nuclear p53 immunoreactivity in ≥ 5% epithelial nuclei [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that IBD patients with IND mucosal changes carried significant risk for progression to neoplasia: 25.2% of patients with IBD-IND developed dysplasia or carcinoma during a mean follow-up of 98.6 months, with an incidence of all neoplasia at 3.2 cases/100 person-years and an incidence of advanced neoplasia at 1.5 cases/100 person-years [ 14 ]. We also reported the diagnostic utility of p53 and cytokeratin 7 in IBD-associated neoplasia [ 17 ]. This study aimed to determine the predictive value of the two markers for neoplasia progression risk in an IBD-IND population.…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial changes were classified as negative for dysplasia, positive for dysplasia (LGD, HGD, or EAC) or IND. Immunohistochemical staining for p53, AMACR, and cyclin D1 was performed on whole tissue sections from Hollande's fixed or formalin-fixed and paraffin-embedded tissue, as described previously [19]. In brief, de-paraffinized tissue sections were stained with antibodies against p53 (clone DO-7, at a 1:20 working dilution; Dako Corp., Carpinteria, CA, USA), AMACR (clone 13H4, at a 1:100 working dilution, Zeta Corp., Sierra Madre, CA, USA), and cyclin D1 (clone SP4, at a 1:100 working dilution; ThermoLabVision, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…who was blinded to the neoplasia outcomes. The expression of p53 was determined as the percentage of epithelial cells in the esophageal columnar tissue showing nuclear staining within a high-power field [19] (Figure 1A). High p53 expression was defined as more than 5% of the epithelial cells in the esophageal columnar tissue showing nuclear staining.…”
Section: Methodsmentioning
confidence: 99%
“…23 Despite the promising findings, the diagnostic utility of CK7 is limited due to frequent reactivity to nondysplastic epithelium (31% of cases) and therefore should not be used as a stand-alone marker. 23 …”
Section: Use Of Immunohistochemistry In the Assessment Of Dysplasiamentioning
confidence: 97%